Evolutionary Dynamics of Multigene Families in Triportheus (Characiformes, Triportheidae): A Transposon Mediated Mechanism? - Yano, Cassia F.; Merlo, Manuel A.; Portela-Bens, Silvia; Cioffi, Marcelo de B.; Bertollo, Luiz A. C.; Santos-Júnior, Célio D.; Rebordinos, Laureana (Frontiers in Marine Science, 2020)
Triportheus (Characiformes, Triportheidae) is a freshwater fish genus with 18 valid species. These fishes are widely distributed in the major river drainages of South America, having commercial importance in the fishing market, mainly in the Amazon basin. This genus has diverged recently in a complex process of speciation carried out in different river basins. The use of repetitive sequences is suitable to trace the genomic reorganizations carried out along the speciation process. In this work, the 5S rDNA multigene family has been characterized at molecular and phylogenetic level. The results showed that other multigene family has been found within the Non Transcribed Spacer (NTS): the U1 snRNA gene. Double-FISH with 5S and U1 probes were also carried out, confirming the close linkage between these two multigene families. Moreover, evidences of different Transposable Elements (TE) were detected within the spacer, thus suggesting a transposon-mediated mechanism of 5S-U1 evolutionary pathway in this genus. Phylogenetic analysis demonstrated a species-specific grouping, except for T. pantanensis, T. aff. rotundatus and T. trifurcatus. The evolutionary model of the 5S rDNA in Triportheus species has been discussed. In addition, the results show new clues for the speciation and evolutionary trend in these species, which could be suitable to use in other Characiformes species.